Penambahan Sari Daun Kelor (Moringa oleifera) terhadap Uji Organoleptik dan Daya Simpan Selai Buah Naga Merah (Hylocereus polyrhizus) - Akmi, Haslindatul; Dharmawibawa, Iwan Doddy; Nofisulastri, Nofisulastri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Red dragon fruit is an immigrant fruit that is liked by many people because it has content and properties that are quite good for health. The production of red dragon fruit from year to year will increase, so that at harvest time the price will drop drastically from usual. On the other hand, red dragon fruit cannot be stored for too long, so in this study an attempt was made to make jam from red dragon fruit flesh mixed with Moringa leaf extract. Moringa leaf extract used has tannin compounds that are useful in food products to extend the shelf life of a food. The purpose of this study was to determine the effect of adding Moringa leaf extract (Moringa oleifera) on organoleptic tests and the shelf life of red dragon fruit jam (Hylocereus polyrhizus). This study used a randomized block design (RAK) consisting of 6 treatments with 4 replications, with different concentrations of Moringa leaf extract, namely (K = 0 ml, P1 = 5 ml, P2 = 15 ml, P3 = 25 ml, P4 = 30 ml, P5 = 50 ml. Based on the results of the study, it was found that the organoleptic test results of red dragon fruit jam (Hylocereus polyrhizus) had an effect on the level of aroma and taste, but had no effect on the color level of the jam. The shelf-life test of red dragon fruit jam (Hylocereus polyrhizus) was able to persisted for 4 days, after the 5th day some of the treatment samples were found to be moldy and after the 7th day almost all red dragon fruit jams were found to be moldy with the number of fungi growing more and more, so that the addition of Moringa oleifera leaf extract was not able to prolong the durability save the red dragon fruit jam (Hylocereus polyrhizus).